Unfolded P53 as a novel lead biomarker for Alzheimer's disease diagnosis: Biomarkers (non‐neuroimaging) / plasma/serum/urine biomarkers. (7th December 2020) - Abate, Giulia; Fowler, Christopher J; Martins, Ralph N; Memo, Maurizio; Uberti, Daniela
Abstract: Background: Blood‐based biomarkers represent a promising choice for early Alzheimer's disease (AD) diagnosis and for evaluating the efficacy of novel disease‐modifying therapeutics. The complexity of the disease, where multiple pathogenetic mechanisms are involved, would require a pragmatic approach that includes a biomarkers panel for an individually‐tailored AD diagnosis. Oxidative stress, reactive oxygen and nitrogen species have been well documented in AD, however the potential use in the clinic of the metalloprotein p53 as a lead biomarker for this devastating neurodegenerative disorder has not yet been thoroughly investigated. Thus, the aim of this study was to evaluate the role of a conformational variant of p53 as a lead biomarker (Up53 2D3A8+ ) in plasma samples from AD at the pre‐clinical and prodromal stages. Method: Plasma samples from Australian Imaging, Biomarkers and Lifestyle cohort (AIBL) biobank were used to evaluate the concentration of Up53 2D3A8+ through immunoprecipitation with the 2D3A8 antibody followed by SRM‐MS. A total of 102 plasma samples was studied, which includes at baseline samples from (a) AD patients, (b) Mild Cognitive Impairments (MCI) patients and (c) cognitive normal (CN) individuals, in addition to samples at a later time‐point from (d) individuals that converted to AD in a period of 18‐72 months, (e) MCI patients that converted to AD in a period of 18‐36 months and (f) MCI patients at baseline that have not declined to AD for a period of 36 months. Through using a standard heavy isotype labelled peptide spiked into clinical sample before the assay such as plasma, the absolute abundance of Up53 2D3A8+ protein isoform or its partial degradation products was measured accurately with a high sensitivity. Result: A specific peptide of Up53 2D3A8+ as signature of clinical AD progression was detected by 2D3A8 immunoprecipitation and quantified by SRM‐MS. This peptide showed a prognostic value with a sensitivity >90%, specificity >85%, PPV around 80%, NPV >95%. Conclusion: The study presented here strongly supports Up53 2D3A8+ as a promising lead AD biomarker, in particular for disease prognosis in its asymptomatic stage. Consequently it may become an indispensable tool for patient stratification for clinical trials that aim for the prevention of dementia stage in AD progression.